Effect of surfactants on honey bees - Goodwin, R.M.; McBrydie, H.M. (New Zealand Plant Protection, 2000)
The toxicity of surfactants applied topically and orally to honey bees (Apis mellifera L) was determined by laboratory bioassays Eleven surfactants (Citowett Pulse Boost Codacide oil Contact Raingard Peptoil Sunspray Ethokem Multifilm and Uptake) were applied topically to anoxiated bees Anoxiating bees and spraying them with water had no significant effect on their survival Four surfactants (Citowett Pulse Boost and Ethokem) were toxic when applied topically Ethokem and Boost also showed oral toxicity Field trials are necessary to assess the actual impact of surfactants As some surfactants were demonstrated to be toxic to bees in laboratory trials which suggests they may be toxic when used in the field they should go through the agrichemical registration process and honey bee warning labels should be included where appropriate